USING DIGITAL BUSINESS SIMULATORS IN ECONOMIC AND MANAGERIAL DEVELOPMENT OF MASTER’S IN INFORMATION TECHNOLOGIES - Dmytro S. Antoniuk; Oleg M. Spirin; Tetiana A. Vakaliuk (Інформаційні технології і засоби навчання)
The article substantiates the use of digital business simulators as the type of digital educational resources for decision-making knowledge, skills, and attitudinal and behavioral readiness development in economic and managerial training for a Master’s in Information Technologies. The use of digital business simulations as the tool for immersive practices implementation in the educational process provides the possibility to conduct imitated experiences to serve an educational and research-related purpose. Contract Design and Principal-Agent dilemma simulation usage allows the modeling of situations realistically imitating reality and helps to form a basic attitude and understanding of contractual design and information asymmetry concepts in the economy and managerial science. The concepts are crucial for future professionals working in IT, interacting in teams, and developing in people- and task-management areas. The use of multi-user simulated environments for educational interaction of the groups of students provides a close to a realistic experience of acting in life- and work-specific situations. These experiences serve to ignite interest, improve motivation to learn, and establish the ground for a further deeper discussion on the topics and formation of the attitudinal and behavioral components of the economic and managerial competence as part of the soft skills of the Master’s in IT students. The educational activity described and analyzed in the article proved to be useful for both educational and research-related purposes. The mistake, made by the organizer of the activity provided additional learning possibilities for the group and valuable input for the research. The students showed involvement, dedication, and active participation in the active learning imitated experience. The group showed learning progress toward conventional optimality in the simulated concepts. Used digital education resources provided acceptable ease of use and satisfying functionality of the analysis tools. The behavioral specifics, based on the gender differences were unpredicted, but valuable results of the educational experience. Further efforts will be put to the improvement of the technical integration of such simulators into the digital educational environment of higher education institutions and the development of methodological support for the use of such simulators in the educational process.